Improving the formability of linear flow split profiles by laser annealing: Verbesserung der Umformbarkeit von Spaltprofilen mittels Laser‐Wärmebehandlung. Issue 12 (14th December 2016) - Niehuesbernd, J.; Monnerjahn, V.; Bruder, E.; Groche, P.; Müller, C.
Abstract : The effect of laser annealing on the mechanical properties of severely deformed low alloy steel is discussed. Two different sets of annealing parameters were used to achieve improvements in formability. The resulting microstructures, tensile properties and hardness distributions are reviewed. Annealing at temperatures around 700 °C with very high heating and cooling rates leads to recrystallization at the surface and moderate grain growth in subsequent layers. The improvement in ductility is proven to be sufficient to prevent cracking during bending operations.